Nanomaterials 2018
DOI: 10.1136/oemed-2018-icohabstracts.803
|View full text |Cite
|
Sign up to set email alerts
|

1601f A new risk grouping concept for high aspect ratio materials – the shaker dustiness test

Abstract: Introduction Because of their unique physico-chemical properties, CNTs have attracted a great deal of research interest and have many promising industrial applications. However, this also increases the exposure potential for workers, raising the need to understand their hazard for an effective occupational health and safety management. CNTs can induce lung inflammation, granuloma formation, fibrosis and cancer in rodents; in particular, MWCNTs are known to induce in vitro markers of remodelling and fibrosis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…test results on nanofibers of known diameter and composition are available for multi-walled carbon nanotubes (MWCNTs) Figure 7.2 in Ref. [8]. Rittinghausen et al reported a positive, fiber-like i.p.…”
Section: Critical Flexural Rigidity To Derive a Cut-off Diametermentioning
confidence: 99%
See 4 more Smart Citations
“…test results on nanofibers of known diameter and composition are available for multi-walled carbon nanotubes (MWCNTs) Figure 7.2 in Ref. [8]. Rittinghausen et al reported a positive, fiber-like i.p.…”
Section: Critical Flexural Rigidity To Derive a Cut-off Diametermentioning
confidence: 99%
“…Carbon nanotubes (CNTs) became famous for being very high modulus materials compared to other nano-and microscale fibers Table 7.3 in Ref. [8]. However, depending on the synthesis method and the measurement technique, MWCNT can show a rather broad variation of elastic modulus values of 1200-20 GPa Table 1 in [30].…”
Section: Critical Flexural Rigidity To Derive a Cut-off Diametermentioning
confidence: 99%
See 3 more Smart Citations